Do patients with young onset Alzheimer's disease deteriorate faster than those with late onset Alzheimer's disease? A review of the literature. (December 2014) - Stanley, Karen; Walker, Zuzana; Koopmans, Raymond; Rosness, Tor
ABSTRACT Background: Young onset Alzheimer's disease (YOAD; onset before 65 years of age) is thought to have a more rapid course and increased rate of progression compared to late onset Alzheimer's disease (LOAD). This assumption appears partly due to important clinical, structural, neuropathological, and neurochemical differences suggesting YOAD is a separate entity to LOAD. The aim in this review was to systematically identify and examine appropriate studies comparing rate of cognitive decline between patients with YOAD and patients with LOAD. Methods: A computer-based literature search was initially undertaken, followed by citation tracking and search of related papers. Primary research studies specifically focused on the rate of cognitive decline between people with YOAD and LOAD were included. Studies were described, critically analyzed, presented, and discussed in the review. Results: Four studies were included, of which three were longitudinal and one was a case-control study. Three of the included studies found a faster rate of decline in patients with YOAD, and one found no difference in rate of decline between the two groups. Conclusions: The findings of the review are mixed and conflicting, and limited by the heterogeneity of the included studies. There is a need for future research to design systematic studies that include sufficient sample sizes and follow-up periods, and control for possible confounding factors such as education level, baseline cognitive impairment, and vascular risk factors. This will help to validate the findings so far and improve our understanding of the rate of cognitive decline in people with YOAD and LOAD.